2021
DOI: 10.1101/2021.10.05.463282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 hijacks neutralizing dimeric IgA for enhanced nasal infection and injury

Abstract: Robust severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection in nasal turbinate (NT) accounts for high viral transmissibility, yet whether neutralizing IgA antibodies can control it remains unknown. Here, we evaluated receptor binding domain (RBD)-specific monomeric B8-mIgA1 and B8-mIgA2, and dimeric B8-dIgA1 and B8-dIgA2 against intranasal SARS-CoV-2 challenge in Syrian hamsters. These antibodies exhibited comparably potent neutralization against authentic virus by competing with human angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Notably, besides the previously published control ZB8 28 , ZCB11 had the strongest binding capability to both RBD and Spike with the same EC 50 values of 20 ng/ml by ELISA (Fig. 2a, Supplementary Table 5).…”
Section: Isolation Of Nabs Against Sars-cov-2 From the Elite Vaccineementioning
confidence: 62%
See 1 more Smart Citation
“…Notably, besides the previously published control ZB8 28 , ZCB11 had the strongest binding capability to both RBD and Spike with the same EC 50 values of 20 ng/ml by ELISA (Fig. 2a, Supplementary Table 5).…”
Section: Isolation Of Nabs Against Sars-cov-2 From the Elite Vaccineementioning
confidence: 62%
“…With vaccinee informed consent, we obtained another blood sample donated by BNT162b2-26 at day 130 after his second vaccination. Fresh PBMCs from BNT162b2-26 were stained for antigen-specific memory B cells (CD19, CD27, IgG) using the 6xHis-tagged SARS-CoV-2 WT spike as the bait as previously described 28 . Spike-specific memory B cells were found in BNT162b2-26 but not in the healthy donor (HD) control (Supplementary Fig.…”
Section: Isolation Of Nabs Against Sars-cov-2 From the Elite Vaccineementioning
confidence: 99%
“…Antibody-mediated disease enhancement has been reported in diverse RNA viral diseases, such as influenza, SARS-CoV-2, Dengue, and human immunodeficiency viruses infections [ [60] , [61] , [62] , [63] ]. One team found that SARS-CoV-2 RBD-specific neutralizing dimeric IgAs isolated from nasal turbinate could facilitate viral infection, transmission, and injury in Syrian hamsters [ 64 ]. Aleyd et al [ 65 ] demonstrated that IgA enhances NETosis as an effective defense mechanism to eliminate pathogens at mucosal surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, assessments of antibody efficacy need to include not only the amount and the affinity of the antibody preparation but also the isotype composition. This is underscored by a report showing that monotherapy with dimeric IgA increased SARS‐CoV‐2 infectivity via DC‐SIGN, suggesting the possibility of antibody‐dependent enhancement (ADE) of infection 29 …”
Section: Introductionmentioning
confidence: 99%
“…This is underscored by a report showing that monotherapy with dimeric IgA increased SARS-CoV-2 infectivity via DC-SIGN, suggesting the possibility of antibody-dependent enhancement (ADE) of infection. 29 In this narrative review we gathered studies that assessed viral load in nasal samples, lower respiratory secretions or serum and compared antibody effects in the nasopharynx, a tissue where antibody might not be as effective to respiratory secretions or serum, tissues where it may be more effective.…”
mentioning
confidence: 99%